Does peer education go beyond giving reproductive health information? Cohort study in Bulawayo and Mount Darwin, Zimbabwe. Issue 3 (8th March 2020) - Mangombe, Aveneni; Owiti, Philip; Madzima, Bernard; Xaba, Sinokuthemba; Makoni, Talent M; Takarinda, Kudakwashe C; Timire, Collins; Chimwaza, Anesu; Senkoro, Mbazi; Mabaya, Simbarashe; Samuelson, Julia; Ameyan, Wole; et al.
Abstract : Objective: Peer education is an intervention within the voluntary medical male circumcision (VMMC)–adolescent sexual reproductive health (ASRH) linkages project in Bulawayo and Mount Darwin, Zimbabwe since 2016. Little is known if results extend beyond increasing knowledge. We therefore assessed the extent of and factors affecting referral by peer educators and receipt of HIV testing services (HTS), contraception, management of sexually transmitted infections (STIs) and VMMC services by young people (10–24 years) counselled. Design: A cohort study involving all young people counselled by 95 peer educators during October–December 2018, through secondary analysis of routinely collected data. Setting: All ASRH and VMMC sites in Mt Darwin and Bulawayo. Participants: All young people counselled by 95 peer educators. Outcome measures: Censor date for assessing receipt of services was 31 January 2019. Factors (clients' age, gender, marital and schooling status, counselling type, location, and peer educators' age and gender) affecting non-referral and non-receipt of services (dependent variables) were assessed by log-binomial regression. Adjusted relative risks (aRRs) were calculated. Results: Of the 3370 counselled (66% men), 65% were referred for at least one service. 58% of men were referred for VMMC. Other services had 5%–13% referrals. Non-referral for HTS decreased with clients' age (aRR: 0.9) but was higher among group-counselled (aRR: 1.16). Counselling by men (aRR: 0.77) and rural location (aRR: 0.61) reduced risks of non-referral for VMMC, while age increased it (aRR ≥1.59). Receipt of services was high (64%–80%) except for STI referrals (39%). Group counselling and rural location (aRR: 0.52) and male peer educators (aRR: 0.76) reduced the risk of non-receipt of VMMC. Rural location increased the risk of non-receipt of contraception (aRR: 3.18) while marriage reduced it (aRR: 0.20). Conclusion: We found varying levels of referral ranging from 5.1% (STIs) to 58.3% (VMMC) but high levels of receipt of services. Type of counselling, peer educators' gender and location affected receipt of services. We recommend qualitative approaches to further understand reasons for non-referrals and non-receipt of services.